DARI BAHASA IBU MENUJU LITERASI SEKOLAH: TANTANGAN PENDIDIKAN MULTIBAHASA PADA WILAYAH RURAL DAN URBAN - Sri Afriani Putri Faisal; Abdul Rahman; Nurhaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia as a multilingual country, has more than 700 regional languages ​​spoken as mother tongues by millions of students. This linguistic diversity makes the transition from mother tongue to learning to read and write in Indonesian a complex challenge, especially in rural and urban areas that have different social and linguistic characteristics. This study aims to systematically examine the challenges of multilingual education in rural and urban areas in Indonesia by reviewing the current literature. This study uses a Systematic Literature Review (SLR) approach by analyzing 25 selected articles from the SINTA, Garuda, and Scopus databases.The results show that rural areas face several challenges, such as a lack of skilled teachers in multilingual education, a shortage of regional language-based teaching materials, and a digital infrastructure gap. Meanwhile, urban areas face challenges such as high linguistic diversity due to the large number of people moving around, changes in mother tongue use due to the dominance of social languages, and the increasing influence of global culture. The research findings also indicate that the Mother Tongue-Based Multilingual Education (MTB-MLE) approach has a positive impact on improving students' early literacy skills. Therefore, it is necessary to have a multilingual education policy that is relevant to the context, collaboration between different sectors, and curriculum development that can accommodate the diversity of Indonesian languages ​​to support equality in the quality of education.